Clinical impact and diagnostic accuracy of 2-[18F]-fluoro-2-deoxy-d-glucose positron-emission tomography/computed tomography (PET/CT) brain imaging in patients with cognitive impairment: a tertiary centre experience in the UK. Issue 1 (January 2017) - Motara, H.; Olusoga, T.; Russell, G.; Jamieson, S.; Ahmed, S.; Brindle, N.; Pillai, A.; Scarsbrook, A.F.; Patel, C.N.; Chowdhury, F.U.
Abstract : Aim: To evaluate the clinical impact of combined 2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG) positron-emission tomography/computed tomography (PET/CT) brain imaging performed in selected patients with cognitive impairment at a tertiary referral centre in the UK, and to assess the accuracy of FDG PET/CT to correctly establish the diagnosis of Alzheimer's dementia (AD) in "real-world" clinical practice. Methods and materials: Using an institutional radiology database, 136 patients were identified for inclusion in the study. FDG PET/CT was performed using a standard technique and interpreted by dual-trained radiologists and nuclear medicine physicians. Standardised questionnaires were sent to the referring clinicians to establish the final clinical diagnosis and to obtain information about the clinical impact of FDG PET/CT. Results: There was a 72% questionnaire return (98/136), with mean patient follow-up of 471 (standard deviation 205) days. FDG PET/CT had an impact on patient management in 81%, adding confidence to the pre-test diagnosis in 43%, changing the pre-test diagnosis in 35%, reducing the need for further investigations in 42%, and resulting in a change in therapy in 32%. There was substantial correlation between the PET/CT diagnosis and final clinical diagnosis with a correlation (k) coefficient of 0.78 ( p <0.0001). The accuracy of FDG PET/CT in diagnosis of AD was 94% (95% confidence interval [CI]: 87–99), with a sensitivity of 87% (95% CI: 75–92) and a specificity of 97% (95% CI: 87–99). Conclusion: FDG PET/CT brain imaging has a significant clinical impact when performed selectively in patients with cognitive impairment and shows high accuracy in the diagnosis of AD in "real-world" clinical practice. Highlights: Dementia is a clinical problem of worldwide concern. Timely clinical diagnosis of dementia can be challenging in some patients. FDG PET/CT is an important diagnostic tool in unexplained cognitive impairment. FDG PET/CT had an impact on clinical management in >80% of these patients. FDG PET/CT had an accuracy of 94% for the diagnosis of Alzheimer's Disease.